Solution
prove
Solution
Solution steps
Manipulating left side
Use the negative angle identity:
Use the negative angle identity:
Manipulating right side
Simplify
We showed that the two sides could take the same form
Popular Examples
prove (csc^2(θ)-1)/(cos(θ))=cot(θ)csc(θ)prove prove sec(a)-cos(a)csc(a)-sin(a)=tan(3a)prove prove cos^2(x)=sin(x)prove prove 1-(cos^2(u))/(1-sin(u))=-sin(u)prove prove tan(θ)(cot(θ)cos(θ)+sin(θ))=sec(θ)prove
Frequently Asked Questions (FAQ)
Is sin(-x)-cos(-x)=-(sin(x)+cos(x)) ?
The answer to whether sin(-x)-cos(-x)=-(sin(x)+cos(x)) is True